PENGARUH PELATIHAN DIGITALISASI KEWIRAUSAHAAN DAN FINANCIAL TECHNOLOGY TERHADAP PENINGKATAN KETERAMPILAN BERWIRAUSAHA SDM: (STUDI PADA ANGGOTA KELOMPOK TUMBUH BERSAMA MUTIARA HARAPAN DAN MASYARAKAT SEKITARNYA) - Anastasya Gladly Nadya Santo; Inas Jihan Nafi'ah; Auliya Mualimah; Aulia Nur Arfani; Intanuari Astuti; Leliya Lisga Lungga; Andarias Vanissaputri; Aisyah Isjayanti (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2024)
Digital entrepreneurship and the application of financial technology skills are the digital age's challenge of entrepreneurship. This study aims to determine the effect of entrepreneurial digitalization and financial technology training on human resource entrepreneurship skills in members of tumbuh bersama mutiara harapan group and the surrounding community who participated in the training. This research is quantitative research with a descriptive approach. The data analysis techniques used are research instrument test, classical assumption test, multiple linear regression analysis test, hypothesis testing, and determination coefficient test. Based on the results of the t test / partial digitalization training variables (X1) and financial technology variables (X2) affect the entrepreneurial skills of human resources (Y). The test results of the coefficient of determination show the variables X1 and X2 are able to explain the variable Y by 53.5% while the rest is explained by other variables.